Research on the Calculation Method of Equivalent Parameters of the Core Wire for the High-Voltage GIL Metal Shell Grounded Through the Copper Bar - Li, Botong; Shi, Lin; Wen, Weijie; Li, Bin; Gu, Tianfeng (Frontiers in Energy Research, 2022)
The calculation method of the equivalent impedance and admittance parameters of the Gas Insulated Line (the Gas Insulated Line is abbreviated as GIL in this paper) grounded by the copper bar is studied and proposed. In consideration of the electrical coupling among the metal shell, the core wire, and the grounding copper bar, the matrix forms and characteristics of GIL impedance and admittance parameters are analyzed. The method of eliminating the coupling among the conductor layers, the grounding copper bar, and the core wire is studied in accordance with the current and voltage boundary conditions. Eventually, the calculation method of equivalent impedance and admittance parameters of the GIL core wire is proposed. The correctness of the calculation method of GIL core wire equivalent parameters is verified by simulation comparisons in PSCAD. This method can obtain the equivalent parameters of the GIL core wire by eliminating the coupling effect of external conductors and simplifies the seventh-order parameter matrix of the multi-layer GIL line to a third-order matrix that only considers the core wire parameters. The calculation speed can be significantly improved for short-circuit current calculation and related analysis of high-voltage AC systems containing GIL by using the equivalent parameters.